Transient Neonatal Zinc Deficiency Caused by a Heterozygous G87R Mutation in the Zinc Transporter ZnT-2 (SLC30A2) Gene in the Mother Highlighting the Importance of Zn2+ for Normal Growth and Development - Maria Consolata Miletta; Andreas Bieri; Kristin Kernland; Martin H. Schöni; Vibor Petkovic; Christa E. Flück; Andrée Eblé; Primus E. Mullis (International Journal of Endocrinology)
Suboptimal dietary zinc (Zn2+) intake is increasingly appreciated as an important public health issue. Zn2+ is an essential mineral, and infants are particularly vulnerable to Zn2+ deficiency, as they require large amounts of Zn2+ for their normal growth and development. Although term infants are born with an important hepatic Zn2+ storage, adequate Zn2+ nutrition of infants mostly depends on breast milk or formula feeding, which contains an adequate amount of Zn2+ to meet the infants’ requirements. An exclusively breast-fed 6 months old infant suffering from Zn2+ deficiency caused by an autosomal dominant negative G87R mutation in the Slc30a2 gene (encoding for the zinc transporter 2 (ZnT-2)) in the mother is reported. More than 20 zinc transporters characterized up to date, classified into two families (Slc30a/ZnT and Slc39a/Zip), reflect the complexity and importance of maintaining cellular Zn2+ homeostasis and dynamics. The role of ZnTs is to reduce intracellular Zn2+ by transporting it from the cytoplasm into various intracellular organelles and by moving Zn2+ into extracellular space. Zips increase intracellular Zn2+ by transporting it in the opposite direction. Thus the coordinated action of both is essential for the maintenance of Zn2+ homeostasis in the cytoplasm, and accumulating evidence suggests that this is also true for the secretory pathway of growth hormone.